Expression and function of the homeodomain-containing protein Hex in thyroid cells - Pellizzari, Lucia (Oxford University Press, 2000)
The homeodomain-containing protein Hex (also named Prh) is expressed in primitive endoderm (during the early phases of development), in some endoderm-derived tissues and in endothelial and hematopoietic precursors. Hex expression is extinguished during terminal differentiation of endothelial and hematopoietic cells as well as in adult lung. Previous investigations have demonstrated that Hex is expressed during early thyroid gland development. No information has been reported on Hex expression in adult thyroid gland or on the function of this protein in follicular thyroid cells. These issues represent the focus of the present study. We demonstrate that Hex mRNA is present in rat and human adult thyroid gland as well as in differentiated follicular thyroid cell lines. In FRTL-5 cells TSH reduces Hex expression. In thyroid cell lines transformed by several oncogenes Hex expression is completely abolished. By using co-transfection assays we demonstrate that Hex is a repressor of the thyroglobulin promoter and that it is able to abolish the activating effects of both TTF-1 and Pax8. These data would suggest that Hex may play an important role in thyroid cell differentiation. Protein–DNA interaction experiments indicate that Hex is able to bind sites of the thyroglobulin promoter containing either the core sequence 5′-TAAT-3′ or 5′-CAAG-3′. The DNA binding specificity of the Hex homeodomain, therefore, is more ‘relaxed’ than that observed in the majority of other homeodomains.